2018
DOI: 10.1111/pan.13501
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of midazolam and zolpidem as oral premedication in children, a prospective randomized double‐blinded clinical trial

Abstract: Summary Background Anxiety associated with pediatric surgery can be stressful. Midazolam is a well‐accepted anxiolytic in this setting. However, there are cases in which this medication is not effective. Zolpidem is a short‐acting nonbenzodiazepine hypnotic drug that is administered orally and has quick onset of action (~15 minutes), and 2‐3 hour duration. Aims Based on the theory that impaired perception following oral zolpidem administration would suppress the development of anxiety, we sought to compare zol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The patients were divided into two groups, one group received 0.5 mg/kg oral midazolam and the other 0.25 mg/kg oral zolpidem. They found that the effects of zolpidem and midazolam on anxiety were not significantly different (14). Our findings are in line with the results of the above study and show the effectiveness of oral zolpidem.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patients were divided into two groups, one group received 0.5 mg/kg oral midazolam and the other 0.25 mg/kg oral zolpidem. They found that the effects of zolpidem and midazolam on anxiety were not significantly different (14). Our findings are in line with the results of the above study and show the effectiveness of oral zolpidem.…”
Section: Discussionsupporting
confidence: 92%
“…The drug was given to the patients at a relatively low dose to prevent excessive sedation that might mask the symptoms of anxiety and would not be obvious to others, including researchers collecting information. Therefore, the dose of drug was set to a value less than similar studies (6,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toddlers (1-3 years old) possibly require a higher dose (1mgkg -1 ) whereas 0,75mgkg -1 seems sufficient for >95% of children more than 3 years old 5,12,13 . Most studies use 0,5mgkg -1 as a 'golden standard' [14][15][16][17][18][19][20][21][22][23][24][25][26] and this is believed to be the most effective dose with least side effects 27 . Some authors endeavor higher doses of oral midazolam.…”
Section: Anxiolysis At Inductionmentioning
confidence: 99%
“…Mask-acceptance scores were significantly (p=0,03) worse in the zolpidem-group. Five participants in the zolpidem group (n=42) showed minor adverse reactions: double vision, visual hallucinations, dysphoria, involuntary tongue movements and excessive sleepiness 14 .…”
Section: B-2 Zolpidemmentioning
confidence: 99%